(untitled) (Teaching and Learning Inquiry, 2020)
Professional development offerings for current and aspiring educational developers can be sparse and neither fully contextually appropriate nor personally relevant given the range of experiences people bring to the field. In the absence of suitable professionalization programs, we created a self-defined professional development approach to support us in our educational developer work. Using a framework for reflective writing, we describe our approach and the strategies we implemented, and we consider at a “meta” level what contributes to the viability or success of our self-defined professional development plan. Measures for assessing success were framed using utilization-focused evaluation. We outline implications for future practice and propose that a self-defined approach to professional development could be adopted and adapted by other current and aspiring educational developers.